Computational Study of Carbon Open-Cages for Controllable Release of Nanoparticles - Sigalas, Mihail M. (Current Nanomaterials, 2017)
Objective: Explore ways to create open and closed cages with graphene nanoparticles (GNPs) by appropriately placing hydrogen atoms on their surfaces. Method: Density Functional Theory (DFT) have been used for geometry optimization of the GNPs. Results: The controllable release of hydrogen and methane entrapped inside the open nanocages have been studied by adjusting the temperature with ab initio molecular dynamic. Conclusion: New type of open cages has been found with seashell-like geometries and partially open cages with a tongue-like structure.
Keywords: Graphene nanoparticles